Direct instruction for hyperactive students class I in elementary school - Izzah, Atikah Nur; Uyun, Fitratul (Jurnal Bidang Pendidikan Dasar, 2025)
The purpose of this research is to find out direct Instruction strategies for hyperactive students in elementary school. This research method applies a qualitative descriptive approach with data collection techniques carried out by observation, interviews, and documentation at SDN Sumbersari 2 Malang City. Research instruments include observation guidelines, interview guidelines, and documentation studies. Data analysis techniques used include data reduction, data presentation, and conclusion drawing. The results showed that direct Instruction strategies based on lectures, practices and exercises, and demonstrations proved effective in improving the understanding, memory, and counting skills of hyperactive students. The role of the accompanying teacher is also very important in ensuring the success of this strategy. The conclusion of this study confirms that a structured and interactive approach can help hyperactive students achieve their academic potential optimally